Analisis Implementasi dan Efektivitas Zakat Produktif dalam Meningkatkan Kesejahteraan Mustahik di BAZNAS Kabupaten Sintang, Kalimantan Barat - Teti Arnita; Ichsan Iqbal; Syahbudi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2026)
Productive zakat is a strategic instrument in the Islamic economic system for empowering mustahik and enhancing sustainable welfare. BAZNAS of Sintang Regency, West Kalimantan, has implemented productive zakat programs through business capital assistance, training, and mentoring; however, program outcomes vary among beneficiaries. This study aims to analyze the implementation of productive zakat programs and identify factors influencing their effectiveness in improving mustahik welfare. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and document analysis. Informants include BAZNAS administrators, mustahik beneficiaries, muzakki, community leaders, and local government representatives. Data were analyzed using an interactive analysis model and supported by descriptive quantitative data comparing mustahik income before and after receiving productive zakat assistance. The findings indicate that productive zakat programs at BAZNAS Sintang Regency have been implemented systematically and contribute to increased income and economic independence among most beneficiaries. Program effectiveness is influenced by amil managerial capacity, the quality of business mentoring, information technology utilization, local government support, and community zakat literacy. This study concludes that productive zakat is an effective economic empowerment instrument when managed professionally, transparently, and sustainably